TIMING ATTACK ANALYSIS ON THE HARDWARE ENCRYPTOR SHIPKA - Петренко, А. Б.; Шматок, О. С.; Шматок, С. А.; Агеєнко, Є. О. (Science-based technologies, 2014)
Nowadays hardware encryptors are often used for information security; despite the equipment are more expensive than analogous software. First of all; it depends on the high level of reliability; which hardware encryptors can provide. One example of hardware encryptors is the personal means of cryptographic information security SHIPKA. It has been substantiated that the personal means of cryptographic information security SHIPKA prone to timing attacks. Algorithms used in RSA cryptosystem; such as Simple Modular Exponentiation; Montgomery reduction; Chinese Remainder Theorem; have been considered. It has been reported how timing attacks can be performed. Blinding has been suggested to be used in SHIPKA as countermeasures to prevent timing attacks on RSA.